STRENGTHENING GOVERNANCE THROUGH PENTAHELIX COLLABORATION: A QUALITATIVE STUDY IN THE ERA OF DIGITAL DISRUPTIONS - Magda Faradiba Mauludia Agung (Halu Oleo University, 2025)
This study explores the strengthening of governance in Indonesia amid the challenges of digital disruption, marked by growing public demands for speed, transparency, and innovation in public services. Using a qualitative approach, data were collected through in-depth interviews with key stakeholders, direct observation of collaborative events, and analysis of documentation related to public sector digital transformation. The findings highlight persistent governance issues, including inconsistent decentralisation, bureaucratic inefficiency rooted in a nepotistic culture, and limited institutional readiness for digital adaptation. To address these challenges, the study investigates the operationalisation of the Pentahelix collaboration model—an inclusive framework that brings together government, academia, business, community groups, and the media. Field data show that this model enhances collaborative governance by leveraging diverse actor capacities in co-creating adaptive and innovative solutions. The Jakarta International Java Jazz Festival is used as a case study to illustrate real-world implementation of the Pentahelix model, revealing how multi-sector synergy contributes to digital transformation, public trust, and institutional resilience. Despite challenges such as digital infrastructure gaps and bureaucratic resistance, the study concludes that sustained multi-actor engagement is essential for building inclusive, future-ready governance. The replication of this collaborative model in other sectors offers significant transformative potential.